INTENSITAS IBU RUMAH TANGGA PEMULUNG DALAM MEWUJUDKAN KEHIDUPAN KELUARGA DI KELURAHAN SAIL KECAMATAN TENAYAN RAYA - Supriadi Pangaribuan; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The work as scavengers is one alternative that is considered suitable work that can be done mother, in addition to domestic affairs remain materilize, mothers can also help improve the economy of families with scavenged. Because the scavenger is a job that does not require expertise, education, and do not have the time or schedule rules binding in the work so that a housewife can complete his homework and working at an unspecified time in accordance with the free time they have. The problem in this research are: How do characteristic housewife scavergers in the village of Sail kecamatan Tenayan Raya. How the implementation of the function of the family for housewife scavergers. The purpose of this study was to determine kerakteristik housewife Sail scavengers in the Kelurahan Sail Kecamatan Tenayan Raya. And to investigate the implementation of a family function for homemakers scavengers. Subjects in this study were housewives who work to help her husband earn a living for his family as a scavenger addition as many as five people. Plus the testimony of the husband who is still working and housewives who work as scavengers over 1 year and have dependents who are still at school. The approach used in this study is a qualitative approach, using purposive sampling technique. While the process of collecting data by conducting interviews, observation and documentation. Most housewives scavengers still carry out its role as a mother. His role as women to run a family function remains largely implemented as a function of economic, affective function, the function of socialization, the protection function. However, a small portion also housewives scavengers workers are still helped by her husband and children first in assist with homework so as to create a division of labor within the family harmonious. Pekanbaru City Government should pay attention to housewives who work as scavengers in the Village TPS Sail along the curb and the city of Pekanbaru. Keywords: Scavenger, family, Dual role